1986
DOI: 10.1007/bf01309880
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of purified glycoprotein gB of herpes simplex virus

Abstract: The efficacy of a herpes simplex virus (HSV) component vaccine consisting of viral glycoprotein gB was examined in a mouse system. Immunization of mice with HSV type 1 (HSV-1) gB emulsified in Freund's complete adjuvant or with HSV-1 gB adsorbed to aluminum gel was fully protective against subsequent challenge with HSV-1 or HSV type 2. Latent infection in the trigeminal ganglion was also prevented by immunization with gB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Envelope protein gB has been shown to induce strong T cell responses in humans (15) (as well as neutralizing antibody [1]). In small-animal models, gB vaccination induced protection from HSV-2 challenge (14). Also, CD8 T cell responses to gB have been shown to control latency and prevent reactivation from dorsal root ganglia in mice infected with HSV-2 (11).…”
mentioning
confidence: 99%
“…Envelope protein gB has been shown to induce strong T cell responses in humans (15) (as well as neutralizing antibody [1]). In small-animal models, gB vaccination induced protection from HSV-2 challenge (14). Also, CD8 T cell responses to gB have been shown to control latency and prevent reactivation from dorsal root ganglia in mice infected with HSV-2 (11).…”
mentioning
confidence: 99%
“…In earlier studies, other workers producing HSV antigen preparations for possible use as vaccines in man and employing NP40 or Triton-X-100 detergents [5,17,24,28,41], have for the most part, not reported which HSV glycoproteins are present in their preparations. The Empigen-extracted SDG preparations described in the present study have been shown to contain four HSV-1 gtycoproteins gB, gC, gD and gE, some of which have been found, as individual glycoproteins, to provide protections in animals against HSV challenge [11,20,25,37,39]. Further characterisation of these SDG preparations with respect to the total number and nature of the proteins present, using Western blotting and radioimmunoprecipitation, are currently underway.…”
Section: Discussionmentioning
confidence: 89%
“…Although vaccines containing a number of surface and perhaps internally located HSV proteins may be required to provide protection against infection, several workers have investigated the possibility of using individual surface glycoproteins as vaccines [7,11,20,25,37,39]. The reason for this is the need for highly-purified preparations in man, and undoubtedly HSV antigen preparations obtained by detergent-extractions from infected cells, will contain unwanted proteins and perhaps other materials, including DNA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To improve the immune response, a subunit vaccine containing gC and gD antigens could be supplemented with recombinant gB, which has been shown to be effective in the mouse model system both by active and by passive immunization (Kino et al 1985(Kino et al , 1986. Since gB seems to carry predominantly nonsequencial epitopes, which are responsible for the immune response (Chapsal and Pereira 1988), this protein might, as expected for gC, be expressed immunogenically in eukaryotic cells rather than in bacteria (Pachl et al 1987;Blacklows et al 1987;Kino et al 1989).…”
Section: Discussionmentioning
confidence: 99%